Environmental Exposures and Autoimmune Diseases: Contribution of Gut Microbiome - Khan, M. Firoze; Wang, Hui (Frontiers in Immunology, 2020)
Environmental agents have gained much attention in recent years for their role in triggering autoimmune diseases (ADs). Increasing evidence has linked environmental exposures, including trichloroethene (TCE), silica, mercury, pristane, pesticides and smoking to higher risk for ADs. However, potential mechanisms by which these environmental agents contribute to the disease pathogenesis remains largely unknown. Dysbiosis of the gut microbiome is another important environmental factor that has been linked to the onset of different ADs. Altered microbiota composition is associated with impaired intestinal barrier function and dysregulation of mucosal immune system, but it is unclear if gut dysbiosis is a causal factor or an outcome of ADs. In this review article, we first describe the recent epidemiological and mechanistic evidences linking environmental/occupational exposures with various ADs (especially SLE). Secondly, we discuss how changes in the gut microbiome composition (dysbiosis) could contribute to the disease pathogenesis, especially in response to exposure to environmental chemicals.